C9ORF72 hexanucleotide repeat expansion in ALS patients from the Central European Russia population - Abramycheva, Natalya Y.; Lysogorskaia, Elena V.; Stepanova, Maria S.; Zakharova, Maria N.; Kovrazhkina, Elena A.; Razinskaya, Olga D.; Smirnov, Andrey P.; Maltsev, Andrey V.; Ustyugov, Alexey A.; Kukharsky, Michail S.; Khritankova, Inna V.; Bachurin, Sergey O.; et al. (Neurobiology of aging, 2015)
Cohorts of amyotrophic lateral sclerosis (ALS) patients and control individuals of Caucasian origin from the Central European Russia (Moscow city and region) were analyzed for the presence of hexanucleotide repeat GGGGCC expansion within the first intron of the C9ORF72 gene. The presence of a large (>40) repeat expansion was found in 15% of familial ALS cases (3 of 20 unrelated familial cases) and 2.5% of sporadic ALS cases (6 of 238) but in none of control cases. These results suggest that the frequency of C9ORF72 hexanucleotide repeats expansions in the Central European Russian ALS patients is significantly lower than in Western European or Northern American ALS patients of Caucasian origin but higher than in Asian ALS patients.